![1)\; \; y=x^3-8x+2\\\\y'=3x^2-8=0\; ,\; \; (\sqrt3x-\sqrt8)(\sqrt3x+\sqrt8)=0\; \; ,\; \; x=\pm \sqrt{\frac{8}{3}}\; ,\\\\znaki\; y':\; \; +++(-\sqrt{\frac{8}{3}})---(\sqrt{\frac{8}{3}})+++\\\\x_{max}=-\sqrt{\frac{8}{3}}}\; \; ,\; \; x_{min}=\sqrt{\frac{8}{3}}\\\\y(-\sqrt{\frac{8}{3}})=-\frac{2}{3}\sqrt{\frac{8}{3}}+8\cdot \sqrt{\frac{8}{3}}+2\; \; ,\; y(\sqrt{\frac{8}{3}})=\frac{2}{3}\cdot \sqrt{\frac{8}{3}}-8\cdot \sqrt{\frac{8}{3}}+2\\\\2)\; \; y=x^4-2x^2+3\\\\y'=4x^3-4x=4x(x^2-1)=4x(x-1)(x+1)=0\\\\x_1=0\; ,\; \; x_2=-1\; ,\; x_3=1\\\\znaki\; y':\; \; ---(-1)+++(0)---(1)+++\\\\x_{min}=-1\; ,\; x_{min}=1\; ,\; \; x_{max}=0\\\\y(-1)=y(1)=2\\\\4)\; \; y=x^4-8x^2+2\\\\y'=4x^3-16x=4x(x^2-4)=4x(x-2)(x+2)=0 1)\; \; y=x^3-8x+2\\\\y'=3x^2-8=0\; ,\; \; (\sqrt3x-\sqrt8)(\sqrt3x+\sqrt8)=0\; \; ,\; \; x=\pm \sqrt{\frac{8}{3}}\; ,\\\\znaki\; y':\; \; +++(-\sqrt{\frac{8}{3}})---(\sqrt{\frac{8}{3}})+++\\\\x_{max}=-\sqrt{\frac{8}{3}}}\; \; ,\; \; x_{min}=\sqrt{\frac{8}{3}}\\\\y(-\sqrt{\frac{8}{3}})=-\frac{2}{3}\sqrt{\frac{8}{3}}+8\cdot \sqrt{\frac{8}{3}}+2\; \; ,\; y(\sqrt{\frac{8}{3}})=\frac{2}{3}\cdot \sqrt{\frac{8}{3}}-8\cdot \sqrt{\frac{8}{3}}+2\\\\2)\; \; y=x^4-2x^2+3\\\\y'=4x^3-4x=4x(x^2-1)=4x(x-1)(x+1)=0\\\\x_1=0\; ,\; \; x_2=-1\; ,\; x_3=1\\\\znaki\; y':\; \; ---(-1)+++(0)---(1)+++\\\\x_{min}=-1\; ,\; x_{min}=1\; ,\; \; x_{max}=0\\\\y(-1)=y(1)=2\\\\4)\; \; y=x^4-8x^2+2\\\\y'=4x^3-16x=4x(x^2-4)=4x(x-2)(x+2)=0](https://tex.z-dn.net/?f=1%29%5C%3B%20%5C%3B%20y%3Dx%5E3-8x%2B2%5C%5C%5C%5Cy%27%3D3x%5E2-8%3D0%5C%3B%20%2C%5C%3B%20%5C%3B%20%28%5Csqrt3x-%5Csqrt8%29%28%5Csqrt3x%2B%5Csqrt8%29%3D0%5C%3B%20%5C%3B%20%2C%5C%3B%20%5C%3B%20x%3D%5Cpm%20%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%5C%3B%20%2C%5C%5C%5C%5Cznaki%5C%3B%20y%27%3A%5C%3B%20%5C%3B%20%2B%2B%2B%28-%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%29---%28%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%29%2B%2B%2B%5C%5C%5C%5Cx_%7Bmax%7D%3D-%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%7D%5C%3B%20%5C%3B%20%2C%5C%3B%20%5C%3B%20x_%7Bmin%7D%3D%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%5C%5C%5C%5Cy%28-%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%29%3D-%5Cfrac%7B2%7D%7B3%7D%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%2B8%5Ccdot%20%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%2B2%5C%3B%20%5C%3B%20%2C%5C%3B%20y%28%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%29%3D%5Cfrac%7B2%7D%7B3%7D%5Ccdot%20%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D-8%5Ccdot%20%5Csqrt%7B%5Cfrac%7B8%7D%7B3%7D%7D%2B2%5C%5C%5C%5C2%29%5C%3B%20%5C%3B%20y%3Dx%5E4-2x%5E2%2B3%5C%5C%5C%5Cy%27%3D4x%5E3-4x%3D4x%28x%5E2-1%29%3D4x%28x-1%29%28x%2B1%29%3D0%5C%5C%5C%5Cx_1%3D0%5C%3B%20%2C%5C%3B%20%5C%3B%20x_2%3D-1%5C%3B%20%2C%5C%3B%20x_3%3D1%5C%5C%5C%5Cznaki%5C%3B%20y%27%3A%5C%3B%20%5C%3B%20---%28-1%29%2B%2B%2B%280%29---%281%29%2B%2B%2B%5C%5C%5C%5Cx_%7Bmin%7D%3D-1%5C%3B%20%2C%5C%3B%20x_%7Bmin%7D%3D1%5C%3B%20%2C%5C%3B%20%5C%3B%20x_%7Bmax%7D%3D0%5C%5C%5C%5Cy%28-1%29%3Dy%281%29%3D2%5C%5C%5C%5C4%29%5C%3B%20%5C%3B%20y%3Dx%5E4-8x%5E2%2B2%5C%5C%5C%5Cy%27%3D4x%5E3-16x%3D4x%28x%5E2-4%29%3D4x%28x-2%29%28x%2B2%29%3D0)
0\; ,\; \; x-3=0\; \; \to \; \; x=3\; ,\; \; x\ne 1\\\\znaki\; y':\; \; +++(1)---(3)+++\; ,\; \; x\ne 1\\\\x_{min}=3\; ,\; \; y_{min}=y(3)=\frac{e^3}{4}" alt="x_1=0\; ,\; \; x_1=-2\; ,\; \; x_2=2\\\\znaki\; y':\; \; ---(-2)+++(0)---(2)+++\\\\x_{min}=-2\; ,\; \; x_{min}=2\; ,\; \; x_{max}=0\\\\y(-2)=y(2)=-14\; ,\; \; y(0)=2\\\\3)\; \; y=\frac{e^{x}}{x^2-2x+1}=\frac{e^{x}}{(x-1)^2}\; ,\; \; ODZ:\; x\ne 1\\\\y'=(\frac{e^{x}}{(x-1)^2})'=\frac{e^{x}(x-1)^2-e^{x}\cdot 2(x-1)}{(x-1)^4}=\frac{e^{x}\cdot (x-1)\cdot (x-1-2)}{(x-1)^4}=\frac{e^{x}(x-3)}{(x-1)^3}=0\\\\e^{x}>0\; ,\; \; x-3=0\; \; \to \; \; x=3\; ,\; \; x\ne 1\\\\znaki\; y':\; \; +++(1)---(3)+++\; ,\; \; x\ne 1\\\\x_{min}=3\; ,\; \; y_{min}=y(3)=\frac{e^3}{4}" align="absmiddle" class="latex-formula">